2021
DOI: 10.3389/fonc.2021.656172
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Related Regulatory Networks of MRPL15 in Non-Small-Cell Lung Cancer

Abstract: BackgroundMitochondrial ribosomal protein L15 (MRPL15), a member of mitochondrial ribosomal proteins whose abnormal expression is related to tumorigenesis. However, the prognostic value and regulatory mechanisms of MRPL15 in non-small-cell lung cancer (NSCLC) remain unclear.MethodsGEPIA, ONCOMINE, Gene Expression Omnibus (GEO), UALCAN, Kaplan–Meier plotter, PrognoScan, LinkedOmics and GeneMANIA database were utilized to explore the expression and prognostic value of MRPL15 in NSCLC. Additionally, immune infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Tumor-infiltrating lymphocyte plays crucial roles in the prognosis of NSCLC ( Fan et al, 2021 ; Zeng et al, 2021 ). First, we used TIMER online analysis tool to examine the relationship between the immune infiltration and the somatic copy number alterations of NCAPG in LUAD.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-infiltrating lymphocyte plays crucial roles in the prognosis of NSCLC ( Fan et al, 2021 ; Zeng et al, 2021 ). First, we used TIMER online analysis tool to examine the relationship between the immune infiltration and the somatic copy number alterations of NCAPG in LUAD.…”
Section: Resultsmentioning
confidence: 99%
“…MMP9 is a matricellular protein associated with extracellular matrix (ECM) remodelling, promoting tumour progression, and modulating the activity of cell adhesion molecules and cytokines (Joseph et al, 2020;Mondal et al, 2020). MRPL15 is a member of mitochondrial ribosomal proteins whose abnormal expression is related to tumorigenesis in lung cancer, epithelial ovarian cancer and so on (Xu et al, 2021;Zeng et al, 2021). PDK4 is a member of PDK family located in the mitochondrial matrix of cells, inhibiting the entry of pyruvate into the TCA cycle by inhibiting pyruvate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has demonstrated that high MRPL15 expression predicts a worse prognosis in non-small cell lung cancer; it revealed potential regulatory networks and demonstrated a negative correlation with immune infiltration (75). MRPL42 is highly expressed in early-stage lung adenocarcinoma (LUAD) tissues and cell lines and is significantly associated with prognosis.…”
Section: Prognosismentioning
confidence: 99%